Real Time Three‐Dimensional Transthoracic Echocardiography of Ruptured Left Sinus of Valsalva Aneurysm to Left Ventricle. Issue 10 (10th August 2013) - Kharwar, Rajiv Bharat; Narain, Varun Shankar; Sethi, Rishi
Mini‐Abstract We report a rare case of a 15‐year‐old patient presenting with complaints of effort dyspnea and palpitations. Two‐dimensional transthoracic echocardiography (TTE) showed aneurysmal dilatation of left sinus of Valsalva which had ruptured into the left ventricle. Also, there was an intimal flap within the sinus of Valsalva aneurysm. The anatomical relationship between the aorta, the aneurysm, and the left ventricle as well as the intimal flap within the aneurysm was clearly delineated with the help of three‐dimensional TTE. After confirmation of the diagnosis with multidetector computed tomography, patient underwent successful surgical repair of the defect.